Dissecting the Role of SAL1 in Metabolizing the Stress Signaling Molecule 3′-Phosphoadenosine 5′-Phosphate in Different Cell Compartments - Ashykhmina, Natallia; Chan, Kai Xun; Frerigmann, Henning; Van Breusegem, Frank; Kopriva, Stanislav; Flügge, Ulf-Ingo; Gigolashvili, Tamara (Frontiers in Molecular Biosciences, 2022)
Plants possess the most highly compartmentalised eukaryotic cells. To coordinate their intracellular functions, plastids and mitochondria are dependent on the flow of information to and from the nuclei, known as retrograde and anterograde signals. One mobile retrograde signalling molecule is the monophosphate 3´-phosphoadenosine 5´-phosphate (PAP), which is mainly produced from 3´-phosphoadenosine 5´-phosphosulfate (PAPS) in the cytosol and regulates the expression of a set of nuclear genes that modulate plant growth in response to biotic and abiotic stresses. The adenosine bisphosphate phosphatase enzyme SAL1 dephosphorylates PAP to AMP in plastids and mitochondria but can also rescue sal1 Arabidopsis phenotypes (PAP accumulation, leaf morphology, growth etc) when expressed in the cytosol and nucleus. To understand better the roles of SAL1 protein in chloroplasts, mitochondria, nuclei and the cytosol, we have attempted to complement the sal1 mutant by specifically cargoing transgenic SAL1 protein to these four cell compartments. Overexpression of SAL1 protein targeted to the nucleus or mitochondria alone, or co-targeted to chloroplasts and mitochondria, complemented most aspects of the sal1 phenotype. Notably, targeting SAL1 to chloroplasts or the cytosol did not effectively rescue the sal1 phenotypes as these transgenic lines accumulated very low levels of SAL1 protein despite overexpressing SAL1 mRNA; suggesting possibly lower stability of the SAL1 protein in these compartments. The diverse transgenic SAL1 lines exhibit a range of PAP levels. The latter needs to reach certain thresholds in the cell for its impacts on different processes such as leaf growth, regulation of rosette morphology, sulfate homeostasis, and glucosinolate biosynthesis. Collectively, these findings provide an initial platform for further dissection of the role of the SAL1–PAP pathway in different cellular processes under stress conditions.